Pengaruh Metode Sosiodrama Terhadap Kemampuan Sosial Emosional Pada Anak Usia 5-6 Tahun - Nur Fadila Pulumoduyo; Jamin, Nunung Suryana; Hardiyanti, Waode Eti (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The aim of this research is to improve the social emotional abilities of children aged 5-6 years through the sociodrama method in Popodu Village, Bolaang Uki District, South Bolaang Mongondow Regency. This research is quantitative research with experimental research methods. The research design used in this research is one group pretest-posttest design. The results of this research were 20 children as subjects. From the calculation results on the pretest it was 14.55 and on the post-test it was 29.55. t test with a significance level of 0.05. The Tcount test result is 19.809 and the Ttable result = 0.05: dk = n-1 (20-1=19) is 1.725, thus Tcount is greater than Ttable (Tcount = 19.809 ≥ Ttable = 1.725). Based on the test criteria that accept Ha: if Tcount ≥ Ttable =0.05; n-1, it can be stated that there is an influence of the sociodrama method on children's social emotional abilities.